Rapamycin Attenuates Endothelial Apoptosis Induced by Low Shear Stress via mTOR and Sestrin1 Related Redox Regulation - Zhang, Junxia; Wang, Zhimei; Zhang, Junjie; Zuo, Guangfeng; Li, Bing; Mao, Wenxing; Chen, Shaoliang (Mediators of Inflammation, 2014)
Background. Studies indicate the dramatic reduction of shear stress (SS) within the rapamycin eluting stent (RES) segment of coronary arteries. It remains unclear about the role of rapamycin in endothelialization of stented arteries where SS becomes low. Since mTOR (mammalian target of rapamycin) pathway is involved in the antioxidative sestrins expression, we hypothesized that rapamycin attenuated low SS (LSS) induced endothelial dysfunction through mTOR and sestrin1 associated redox regulation. Methods and Results. To mimic the effect of LSS on the stented arteries, a parallel plate flow chamber was used to observe the interplay of LSS and rapamycin on endothelial cells (ECs). The results showed LSS significantly induced EC apoptosis which was mitigated by pretreatment of rapamycin. Rapamycin attenuated LSS induced reactive oxygen species (ROS) and reactive nitrogen species (RNS) production via prohibition of sestrin1 downregulation. Activities of mTORC1 and mTORC2 were detected contradictorily modulated by LSS. Inhibition of rictor expression by target small interfering RNA (siRNA) transfection prohibited sestrin1 downregulation induced by LSS, but inhibition of raptor did not. Conclusions. Rapamycin may prohibit sestrin1 downregulation through targeting mTORC2 in appeasing LSS induced EC oxidative apoptosis. Our results provide the in vitro evidence to explain the pathophysiology of RES stented arteries.